Synergistic Roles of Biphasic Ethylene and Hydrogen Peroxide in Wound-Induced Vessel Occlusions and Essential Oil Accumulation in Dalbergia odorifera - Cui, Zhiyi; Yang, Zengjiang; Xu, Daping (Frontiers in Plant Science, 2019)
The heartwood of Dalbergia odorifera (D. odorifera), named “Jiang Xiang” in traditional Chinese medicine, is highly valuable. Mechanical wound induced the production of “Jiang Xiang” in D. odorifera. Ethylene and hydrogen peroxide (H2O2) are proposed to play vital roles in wound signaling, however little is known about the role of ethylene or H2O2 in the wound-induced formation of vessel occlusions and biosynthesis of “Jiang Xiang” in D. odorifera. In this study, the pruning of D. odorifera saplings resulted in the synergistic biosynthesis of biphasic ethylene and H2O2, which was followed by formation of vessel occlusions and “Jiang Xiang” in the pruned stems. In this progress, the H2O2 production stimulated higher biosynthesis of ethylene. Treatments with aminoethoxyvinylglycine (AVG), an inhibitor for ethylene biosynthesis and ascorbate (AsA), a scavenger of H2O2, markedly reduced the production of ethylene and H2O2 respectively, the percentage of vessels with occlusions (PVO), oil content, and the amount of “Jiang Xiang” formed. These results indicate that ethylene and H2O2 might be important wound signals in D. odorifera that induce vessel occlusions and formation of “Jiang Xiang”, and thus ethylene and H2O2 might play vital roles in “Jiang Xiang” formation in pruned stems of D. odorifera.